The subgroups of the human remains trade on Instagram. A case study. - Bach, Caroline (Mortality, 2026)
This case study on the human remains trade on Instagram examines the different sub-groups which shape this market. By considering the trading history of bones and associated artefacts as well as symbolic significance assigned to the human cranium, the study aims to unravel underlying patterns. It is assumed that skulls are sold and bought more frequently, according to their historically developed value. The study tries to examine which groups handle crania the most, while also focusing on their respective (self-) display. A dataset of 2,993 images stemming from 12 different Instagram accounts selling and/or collecting human remains was created. To evaluate the ratio of crania to other objects sold/collected, an object recognition model was trained. Results show that human crania are the most frequently obtained item. Gathered data also suggests a relatively clean split between two distinct subgroups: Ethnology-associated and Dark culture-associated profiles. The former is characterised by their self-association with science, history and spirituality, while the latter is shaped by their self-association with death and demise. When regarding the trading history of human remains, this split can be observed since its beginning (17−19 centuries).Additionally, both groups are united in their perception of human remains in a positive way.